2009
DOI: 10.1212/wnl.0b013e3181bd82a7
|View full text |Cite
|
Sign up to set email alerts
|

“Frontotemporoparietal” dementia

Abstract: Patients carrying the c.709-1G>A mutation in the PGRN gene showed heterogeneous clinical and neuropsychological features and commonly developed corticobasal syndrome as the disease progressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…However, as is the case with his brother, clinical presentations of PNFA due to PGRN mutation are also frequent [22]. Several studies have confirmed this strong association between PNFA and PGRN mutations with the typical FTLD-U/TDP-43 pathology [21,2325]. In particular, similar to the brother’s pathological findings, FTLD-U, type 3 pathology, was found to be most commonly associated with the clinical phenotype of PNFA [26].…”
Section: Discussionmentioning
confidence: 92%
“…However, as is the case with his brother, clinical presentations of PNFA due to PGRN mutation are also frequent [22]. Several studies have confirmed this strong association between PNFA and PGRN mutations with the typical FTLD-U/TDP-43 pathology [21,2325]. In particular, similar to the brother’s pathological findings, FTLD-U, type 3 pathology, was found to be most commonly associated with the clinical phenotype of PNFA [26].…”
Section: Discussionmentioning
confidence: 92%
“…We previously described a prevalent ancestral c.709-1G>A mutation related to Basque population [17], [18]. The c.709-1G>A mutation results in null allele, as most of the pathogenic mutations described up to now, suggesting that FTLD in these families results from PGRN haploinsufficiency [5].…”
Section: Introductionmentioning
confidence: 89%
“…The penetrance reaches 90% at age 70 years [27, 28, 29, 30]. A wide spectrum of cognitive, behavioral, and motor features in FTDP-17 is associated with PGRN mutations, but the particular type of mutation does not predict the clinical syndrome [27, 28, 29, 31, 32]. PGRN mutations are usually associated with bvFTD, but unlike MAPT mutation carriers, an isolated language dysfunction and primary progressive aphasia syndrome (PPA) can be also observed [3].…”
Section: Clinical Genetics General Characteristic and Parkinsonimentioning
confidence: 99%